Penerapan Konsep Hifz al-Daulah untuk Menangani Disintegrasi Bangsa - Abdalla, Aufa Ulil Abshar; Frambudi, Satmoko Aji; Ubaidillah, Muh. Hafidh; Musyafaah, Nur Lailatull (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Radicalism can arise from various factors, including religious, economic, political, and social issues. This can cause conflict that increases the potential for social disintegration. In this context, an Islamic legal approach that focuses on the principle of maqasid al-shari’ah becomes important. This study aims to discuss the concept of hifz al-daulah to deal with the phenomenon of radicalism and social conflict in post-reformation Indonesia. This study is library research because the data comes from books and journals. The collected data are analyzed descriptively. This study concludes that radicalism and social conflict have increased post-reformation. To overcome this, it is necessary to instill and socialize the importance of national unity based on maqasid al-shari’ah. Maqasid al-shari’ah emphasizes an understanding of the objectives of Islamic law, including hifz al-ummah, namely the principle of protecting the state, justice, and community welfare. Understanding and implementing the principle of hifz al-daulah in maqasid al-shari’ah is important as an effort to solve social conflict problems and build a harmonious and peaceful society in Indonesia.